Dynamical relaying can yield zero time lag neuronal synchrony despite long conduction delays - Vicente, Raul (National Academy of Sciences, 2008)
Multielectrode recordings have revealed zero time lag synchronization among remote cerebral cortical areas. However, the axonal conduction delays among such distant regions can amount to several tens of milliseconds. It is still unclear which mechanism is giving rise to isochronous discharge of widely distributed neurons, despite such latencies. Here, we investigate the synchronization properties of a simple network motif and found that, even in the presence of large axonal conduction delays, distant neuronal populations self-organize into lag-free oscillations. According to our results, cortico–cortical association fibers and certain cortico–thalamo–cortical loops represent ideal circuits to circumvent the phase shifts and time lags associated with conduction delays.